Designing Cash Transfer Programs for an Older Population: The Mexican Case - Aguila, Emma (J Econ Ageing, 2016)
Aging populations and the prevalence of poverty in old age have led to the introduction of noncontributory pensions in many countries. We consider a number of alternative targeting approaches and simulate their effects in an empirical application in the State of Yucatan, Mexico. We compare the approaches with respect to leakage, under-coverage, and their effects on government budgets. We are also able to compare the simulated effects of one alternative with the observed effect of a recently introduced demogrant and find that the simulation is a close approximation of the empirical outcomes. We discuss issues of implementation and political feasibility.